Mary's penny - Landman, Tanya; Holland, Richard, 1976-; Candlewick Press (Somerville, Mass. : Candlewick Press, 2010)
In this retelling of a classic folk tale, a farmer learns that the best man for the job of farm manager is a girl, as his clever daughter bests his brawny sons in a competition.
American Library Association Amelia Bloomer Project (2011)
Elementary Grade.
Accelerated Reader
Reading Counts!
720
Keywords: Sex role -- Juvenile fiction; Farms -- Juvenile fiction; Competition -- Juvenile fiction; Feminism -- Juvenile fiction; Music -- Juvenile fiction; Folklore; American Library Association Amelia Bloomer Project -- 2011.